PROSEDUR PENGAWASAN BPH MIGAS TERHADAP PIUTANG USAHA PADA PT. XYZ - Oslan Hadi, (2020)
BPH Migas is a body established to conduct oversight arrangements for the supply and distribution of Oil and Gas Fuels and Transportation of Natural Gas through pipelines in Downstream Business Activities. To carry out operational activities, BPH Migas cooperates with PT XYZ to conduct sales activities whether it is cash sales or credit sales. However, credit sales activities have a very high risk that must be monitored by BPH Migas in order to be achieved. accounts receivable control procedures carried out by BPH Migas and provide understanding to the author so that he can think in accordance with the reality in the field. Based on the results of the final project report shows that BPH Migas has conducted good supervision of PT. XYZ on uncollectible receivables by reviewing and analyzing the condition of receivables which is done regularly.